Time to care? The effects of retirement on informal care provision - Björn Fischer; Kai-Uwe Müller (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper analyzes the impact of a reduction in women's labor supply through retirement on their informal care provision. Using SOEP data from the years 2001- 2016 the analysis addresses fundamental endogeneity problems by applying a fuzzy regression discontinuity design. We exploit early retirement thresholds for women in the German pension system as instruments for their retirement decision. We find significant positive effects on informal care provided by women retiring from employment at the intensive and extensive margin that are robust to various sensitivity checks. Women retiring from full-time employment, highly educated women and women providing care within the household react slightly stronger. Findings are consistent with previous evidence and underlying behavioral mechanisms. They point to a time-conflict between labor supply and informal care before retirement. Policy implications are far-reaching in light of population aging. Prevalent pension reforms that aim to increase life-cycle labor supply threaten to reduce informal care provision by women and to aggravate the existing excess demand for informal care.
Keywords: J22; J14; J18; J26; H43; H55; 330; retirement; informal care; regression discontinuity; age threshold